[OP.8B.02] ARTERIAL STIFFNESS IN PATIENTS WITH OBSTRUCTIVE SLEEP APNEA SYNDROME: AN INDIVIDUAL META-ANALYSIS OF CONTRIBUTING FACTORS. (September 2016) - Tamisier, R.; Borel, J.; Millasseau, S.; Galerneau, L.; Destors, M.; Perrin, M.; Pepin, J.
Abstract : Objective: Obstructive sleep apnea syndrome (OSA) is associated with cardiovascular co-morbidities and increased mortality. Arterial stiffness, and more specifically its gold standard pulse wave velocity (PWV) is a recognized independent strong predictor of cardiovascular events and mortality. Several studies have shown that PWV is elevated in OSA patients and might be improved by treatment with continuous positive airway pressure. However the respective impact of traditional risk factors for elevated arterial stiffness on the relationship between OSA and PWV has not been evaluated. Design and method: Data from participants involved in 10 studies involving OSA and performed by our group were pooled. In all studies, PWV was measured with the same technic (Complior SP, Alam Medical, France). Results: The cohort included 901 subjects (age: 56 ± 12 (mean ± SD) - 73% male - 84% with confirmed OSA syndrome). BMI varied from 15 to 81 kg/m2 (30 ± 7) with 22%, 39% 18%, 12 and 9% with normal, overweight, obese, severe obesity and morbid obesity respectively. PWV ranged from 5.3 to 20.5 m/s (10.4 ± 2.3). In a univariate analysis, PWV was strongly related to age (p < 0.0001), gender (p < 0.0001), systolic blood pressure (p < 0.0001), presence of diabetes (p < 0.0001) and to BMI class (p < 0.01). It was only moderately related to total cholesterol (p < 0.01), mean nocturnal saturation (p = 0.03) and Epworth sleepiness scale (p < 0.01) and was not related to apnea-hyponea index (p = 0.25) nor to sleep time with oxygen saturation below 90% (p = 0.42). In a backward multivariate analysis, OSA parameters did not independently contribute, only age, systolic blood pressure, BMI class, diabetes and total cholesterol remained in the model. Conclusions: Our individual meta-analysis shows that PWV values in OSA patients is mainly driven by the standard classical risk factors: age, blood pressure and BMI. Apnea parameters per se, have little influence independently of the standard confounding factors. While treating OSA symptoms is important for patient quality of life, managing the whole cardiovascular risk implies combined therapies addressing the overall cardiovascular risk.